Combined Humeral Head and Shaft Fractures: Outcome Following Intramedullary Nailing and Plating - Firas Souleiman; Jan Theopold; Ralf Henkelmann; Georg Osterhoff; Torsten Pastor; Boyko Gueorguiev; Johannes Fakler; Pierre Hepp (Medicina, 2023)
Background and Objectives: Combined fractures of the humeral head and shaft (FHS) are rare but frequently involve an intermuscular fracture as its characteristic pattern. The aim of this retrospective study was to investigate intramedullary nailed and plated FHS in terms of outcomes and complications. Materials and Methods: The present study included patients with FHS, treated via either intramedullary nailing or plating within a period of 10 years, with a minimum follow-up of 12 months. Functional outcome was assessed using the age- and sex-adapted Constant–Murley Score (CMS-K). Rates of complications and revision surgeries were registered. Results: Twenty-five patients (18 females, 7 males, age 60.1 ± 14.2 years, range 23–76 years) were included in the study. Nailing was performed in 16 patients (12 females, 4 males, age 62.6 ± 12.4 years), whereas plating was executed in nine patients (6 females, 3 males, age 55.8 ± 17.0 years). Follow-up among all patients was 45.1 ± 26.3 months (range 12–97 months). CMS-K was 70.3 ± 32.3 in the nailing group, with reoperation in four cases, and 76.0 ± 31.0 in the plating group, with one reoperation (p = 0.42). Patients with no metaphyseal fragment displacement (n = 19; CMS-K 76.7 ± 17.3) demonstrated significantly better functional outcomes versus those with secondary displacement of the metaphyseal fragments (n = 6; CMS-K 60.0 ± 17.1), p = 0.046. Conclusions: Comparable acceptable clinical outcome is obtained when comparing nailing with additional open cerclage or lag-screw fixation techniques versus plating with open reduction. However, a higher revision rate was observed after nailing. The correct metaphyseal fragment fixation seems to be crucial to avoid loss of reduction and hence the need for revision surgery, as well as a worse outcome.